(3GdEfLjds
(3ChdgG (B:s
(3fHJOF HYhf Gddg hJhajbg HcJGHI agQSI EUMGMGJ GdHTGQI GdebOSI GdJi bGdgG GdQhM GdbOS s
(3BNQgG (B:s
(3jhLO CTjGA cKjQI eeG YedgG EjShY dh cJHJ hGMOkG hGMOkG cedJ HTGQI GdbOjS GdYXje jhMfG GdKGdK YTQ HYhf Gddg JYGdi s
(3fSNI KGdKIs
(3Je fSN gPG GdeNWhW SfI (B1789 (3bes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B175s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdOjGfGJ GdCNQis